Pension program for the welfare of older adults and rural poverty in the State of Puebla. - Cruz de los Ángeles, José Aurelio; Juárez-Sánchez, José Pedro; Cortés Sánchez, Mariana Betzaidet (Agricultura, Sociedad y Desarrollo, 2025)
Given the growing number of people aged 65 years or older in vulnerable situations in Mexico, the Pension for the Well-being of Older Adults (PPBAM) program was implemented in 2018. This research was designed to analyze the relationship between the PPBAM and the situation of poverty and deprivation among the population over 65 years of age, in rural and urban areas of the State of Puebla. Using data from the National Council for the Evaluation of Social Development Policy (CONEVAL) and a Probit model, we estimated for the probability that older adults living in conditions of poverty, both with and without the program’s transfers, identifying patterns and differences between urban and rural areas, as well as between men and women. Results indicate that the PPBAM in the State of Puebla significantly influenced the probability that the population over 65 years of age lives in conditions of poverty (8.4%), revealing differentiated effects between urban (7.9%) and rural (9.7%) areas. The program coverage is higher in rural areas (24%) than in urban areas (21%), however, rural areas continue to present greater deficiencies in terms of food, health, education, social security, quality and housing spaces. Regarding gender allocation, women represent 56% of beneficiaries, which reduces their probability of falling into poverty by 8.8%. In conclusion, although the PPBAM has reduced poverty among the population over 65 years of age, especially among rural women, poverty and extreme poverty continue to affect this population group, so we recommend reevaluating the distribution and prioritization of support,